TYPE OF ERROR ON ARTICLES IN STUDENTS’ WRITING - Lilik Yuliawati; Aprillia; Endang Sri Andayani (LPPM Universitas HKBP Nommensen, 2020)
In learning English as foreign language, Indonesian learners may produce errors since the structure of their first language is different with the English as the foreign language. Errors also exist when they use articles in English. The objective of the research is to know students’ understanding in using articles. Besides, this research also aims to know what type of error mostly appears in students’ writing. This research is a descriptive research combined with error analysis methodology using Surface Strategy Taxonomy. The research participants were 90 students of Bina Sarana Informatika University majoring Communication Science. The result shows that most of the students have some difficulties in using articles. The most common errors made by students are omission errors. Whereas, the second most common errors which appear in students’ writing is addition error which number is not much different with misformation errors. The least type of error which exists in students’ writing is misordering error.